Understanding level of Gharar concept among ACIS students in UiTM Puncak Alam / Muhamad Haikaluddin Muhamad Husli - Muhamad Husli, Muhamad Haikaluddin (2019)
A study on understanding level of gharar concept among ACIS Students in UiTM Puncak Alam. The total number of student involved is 397 people (population). The method that has been used are quantitative that is a questionnaire through the google form. The result showed that the student of ACIS had a moderate level of understanding of gharar concept on the objectives of the study. In conclusion, there is still a lot of effort and knowledge in other to understand about the concept of gharar especially to the whole society.